Diversity of saprobic fungi on Magnoliaceae - Rampai Kodsueb (2018)
The diversity of fungi found on woody litter of three genera of plants in the family Magnoliaceae is reported and the communities are compared. Saprobic fungi were investigated from 150 samples of decaying woody litter of Magnolia liliifera, Manglietia garrettii and Michelia baillonii. Two-hundred and thirty-nine fungi were identified comprising 92 ascomycetes, 4 basidiomycetes and 143 anamorphic fungi. Corynespora cassiicola (60% frequency of occurrence) was the most common taxon found on Magnolia liliifera samples. Ellisembia opaca and Phaeoisaria clematidis with 27.5% frequency of occurrence were the dominant species from Manglietia garrettii, while Annellophora phoenicis and Ellisembia adscendens (18%) were the most commonly encountered species from Michelia baillonii. Distinct fungal communities were found on samples of the three tree species. In terms of the numbers of taxa recovered, fungi were more diverse on Michelia baillonii than on the other two genera, although the common genera of fungi obtained from woody litter of each host were similar. Seasonal effect on the fungal communities was investigated. Dry season samples supported a significantly more diverse fungal community than samples from the wet season. Relatively few species of woody fungi recorded in this study had been previously recorded from wood samples by other researchers.